Treasury Single Account (TSA) in Nigeria - Emovon, Felix Osayabor; Ozele, Clement (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
The purpose of this paper is to examine Treasury Single Account (TSA) in Nigeria: A catalyst for blocking financial leakage in public sector. Treasury Single Account (TSA) is a public accounting system in which all government taxes and income are gathered into a single account, which is normally kept by the Apex bank, the country’s Central Bank, and all payments are made through this account as well. The TSA policy idea was initiated and introduced by the former president, Dr. Goodluck Ebele Jonathan administration, who set a February 2015 deadline for the implementation of the initiative, but did not go ahead with it due to pressures, particularly from the banking sector, to soft pedal on the implementation due to the potential negative impact on the economy. However, the Treasury Single Account (TSA) was established when President Muhammadu Buhari took office. The study’s goal is to determine the value of TSA to the Nigerian economy. The purpose of this conceptual paper is to conduct a literature study on Treasury Single Accounts (TSA) in Nigeria. The library technique was used for this study, which focuses on a content review of existing literature. We concluded that the Treasury Single Account platform has significantly reduced financial leakages in revenue generation while also promoting transparency and accountability in the public financial system. We recommended that the government should review the Treasury Single Account policy to specifically safeguard the financial autonomy of some sectors, for example, educational sector.